Sustainable exploitation of marine fishes with an emphasis on overexploited fish stocks - Rahman, Mohammad Mustafizur (2016)
2000, the production of some fishes such as yellowstripe scad and other carangids are decreasing very rapidly. An intensive research is needed for an urgent basis to find out the actual reason of reducing production of these species. However, the possible reason of dramatic reduction in catch might be due to over exploitation. Once any fish stock is overexploited, it produces lower yields than their biological and ecological potential. Therefore, proper management is urgently needed for sustainable production to ensure long-term sustainability of these fishes. To recover overexploited stock many suggestions has been proposed in the literature. After synthesizing literatures, two main approaches can be proposed for sustainable fisheries production: (i) establishing protected areas, or (ii) limiting capacity and number of fishing vessels, and the allocation of access rights. Continuous data collection and their analysis are prerequisite for the successful of both approaches. Collaboration between scientists, policymaker and fishers is extremely valuable in managing fisheries for sustainable production. Apart from these, managing competing uses such as fishing industry, aquaculture, energy companies, shipping companies, government interests and conservation groups, and reducing by-catch should also be considered for sustainable fisheries production.